TOTAL QUALITY MANAJEMEN DAN DAYA SAING PERUSAHAAN SEBAGAI ANTESENDEN KEPUASAN PELANGGAN MENGHADAPI PERDAGANGAN BEBAS - Respati, Respati (Fakultas Ekonomi, UIN Maliki Malang, 2010)
Manufacturers in Indonesia face new challenge related to prevailing free trade of CAFTA 2010 especially for imported products from Cina. This phenomenon provides a gab for further researchs to have a qualtitative research study on operational management which related to the implementation of Total Quality Management, competitive ability and customer satisfaction. This journal presents the phenomenon of prevailing free trade of CAFTA and some concepts, as well as measurement for TQM variables, Competitive ability of the company and customer satisfaction. Objective of this journal is expected to be able to assist the next researchers who want to conduct a research study on operational management, especially that concern to TQM, competitive ability of the company and customer satisfaction.